The WASP Model: A Micro-Macro System of Wave-Schrödinger-Plasma Equations for Filamentation (Communications in Computational Physics, 2018)
In this paper, we model laser-gas interactions and propagation in some extremeregimes. After a mathematical study of a micro-macro Maxwell-Schrödingermodel [1] for short, high-frequency and intense laser-gas interactions, we propose toimprove this model by adding a plasma equation in order to precisely take into accountfree electron effects. We examine if such a model can predict and explain complexstructures such as filaments, on a physical and numerical basis. In particular, wepresent in this paper a first numerical observation of nonlinear focusing effects usingan ab-initio gas representation and linking our results with existing nonlinear models.